Screen-printed immunosensor modified with carbon nanotubes in a continuous-flow system for the Botrytis cinerea determination in apple tissues - Fernández Baldo, Martín Alejandro (2009)
Botrytis cinerea is a plant-pathogenic fungus that produces the disease known as grey mould in a wide variety of agriculturally important hosts in many countries. This paper describes the development of an immunosensor coupled to carbon-based screen-printed electrodes (SPCE) modified with multi-walled carbon nanotubes (CNTs), which show a rapid and sensitive determination of B. cinerea in apple tissues (Red-delicious) using a competitive immunoassay method. Both the infected plant tissue sample and the B. cinerea-specific monoclonal antibody are allowed to react immunologically with the B. cinerea purified antigens immobilized on a rotating disk. Then, the bound antibodies are quantified by a horseradish peroxidise (HRP) enzyme labeled second antibodies specific to mouse IgG, using 4-tertbutylcatechol (4-TBC) as enzymatic mediators. The HRP, in the presence of hydrogen peroxide, catalyses the oxidation of 4-TBC to 4-tertbutyl o-benzoquinone. The electrochemical reduction back to 4-TBC is detected on SPCE-CNT at -0.15 V. The response current is inversely proportional to the amount of the B. cinerea antigens present in the fruit sample. The time consumed per assay was 30 min and the calculated detection limits for electrochemical method and the ELISA procedure are 0.02 and 10 μg mL-1, respectively. Moreover the intra- and inter-assay coefficients of variation were below 7%. This electrochemical immunosensor promises to be usefully suited to the detection and quantification of B. cinerea in apparently healthy plant prior to the development of the symptoms.